2005
DOI: 10.1523/jneurosci.0302-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Synapse-Specific Regulation of AMPA Receptor Subunit Composition by Activity

Abstract: We examined the changes that arise when neurotransmitter release is inhibited in a subpopulation of hippocampal neurons in coculture with normally active neighbors. Subsets of neurons were presynaptically silenced by chronic expression of tetanus toxin light chain tagged with cyan fluorescent protein (TNTCFP). Surprisingly, silenced neurons formed as many presynaptic terminals as their active neighbors when grown together on glial microislands. However, silenced neurons could not recruit the AMPA-type glutamat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
61
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(68 citation statements)
references
References 56 publications
6
61
1
Order By: Relevance
“…Interestingly, local synaptic activity reduces the diffusional exchange of GluR1 between synaptic and extrasynaptic domains, resulting in postsynaptic accumulation of GluR1-containing AMPAR. In contrast, at neighbor inactive synapses GluR1 was found to be highly mobile (Ehlers et al, 2007), in agreement with an earlier study showing that synapsespecific silencing of neurotransmission causes a reduction in synaptic GluR1-containing AMPARs, in comparison to nearby active synapses (Harms et al, 2005).…”
Section: Vesicular Traffic Synaptic Targeting and Lateral Membrane Dsupporting
confidence: 91%
“…Interestingly, local synaptic activity reduces the diffusional exchange of GluR1 between synaptic and extrasynaptic domains, resulting in postsynaptic accumulation of GluR1-containing AMPAR. In contrast, at neighbor inactive synapses GluR1 was found to be highly mobile (Ehlers et al, 2007), in agreement with an earlier study showing that synapsespecific silencing of neurotransmission causes a reduction in synaptic GluR1-containing AMPARs, in comparison to nearby active synapses (Harms et al, 2005).…”
Section: Vesicular Traffic Synaptic Targeting and Lateral Membrane Dsupporting
confidence: 91%
“…The finding of evidence for retrograde communication does not exclude the additional possibility of orthograde signaling as a further mechanism of transsynaptic coordination. Orthograde signaling has been invoked to explain how presynaptic activity regulates the gathering together of GluA1 (11,24,49). Full coordination might require a combination of signaling in both directions.…”
Section: Role Of Rapid Ampar-dependent Retrograde Signaling To Presynmentioning
confidence: 99%
“…In principle, coordination could arise from a physical linkage of pre-and postsynaptic elements (discussed in ref. 13) or from a primary up-regulation on one side that drives secondary changes on the other (11,23,24).Additional uncertainty exists regarding the time scale of adaptive changes. At the fly neuromuscular junction (NMJ), adaptation to inactivity depends critically on acute changes in physiological function (25)(26)(27).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Because a single postsynaptic cell contains inputs from multiple neurons, inhibited synapses (SYNYFP plus TNTCFP) should be surrounded by actively releasing presynaptic terminals originating from untransfected neurons (detected by endogenous synapsin). To test the validity of this system, the authors demonstrated that terminals positive for SYNYFP and TNTCFP contain lower levels of VAMP2, suggesting that TNTCFP was indeed functional [Harms et al (2005), their Fig. 1 (http:// www.jneurosci.org/cgi/content/full/25/ 27/6379/FIG1)].…”
mentioning
confidence: 99%